Implementation of the INTERGROWTH‐21st Project in Kenya. (16th May 2013) - Carvalho, M; Vinayak, S; Ochieng, R; Choksey, V; Musee, N; Stones, W; Knight, HE; Cheikh Ismail, L; ,
Abstract : Please cite this paper as: Carvalho M, Vinayak S, Ochieng R, Choksey V, Musee N, Stones W, Knight H, Cheikh Ismail L, for the International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ). Implementation of the INTERGROWTH‐21 st Project in Kenya. BJOG 2013; 120 (Suppl. 2): 105–110. The African site in the INTERGROWTH‐21 st Project was Parklands, a wealthy suburb of Nairobi, Kenya, with a largely middle‐to‐high socio‐economic status population. There are three hospitals with obstetric units in Parklands, with approximately 4300 births per year. The Newborn Cross‐Sectional Study (NCSS) sample was drawn from all three hospitals, covering 100% of births in this target population. The Fetal Growth Longitudinal Study (FGLS) sample was recruited from antenatal clinics serving these hospitals, using the eligibility criteria in the INTERGROWTH‐21 st protocol. Special activities to raise awareness of the study included securing media coverage and distributing leaflets in antenatal clinic waiting rooms. FGLS required women to be recruited in the first trimester; therefore, a major challenge at this study site was the high background frequency of first antenatal consultations in the second trimester. The problem was overcome by the study awareness campaign, as a result of which more women started attending antenatal care earlier in pregnancy.